STUDY OF COMMUNITY PARTICIPATION IN DEVELOPMENT OF NGADAS TRADITIONAL TOURISM VILLAGE IN PONCOKUSUMO DISTRICT, MALANG REGENCY - K P Linggarjati; G Prayitno; A D Wicaksono (Diponegoro University, 2019)
The development of a tourism village, from the beginning of the planning to the evaluation process must involve the local community as a form of community empowerment as the goal of tourism development that listed in Indonesian Tourism Master Plan year of 2011- 2025. It was revealed that the community tourism objects of the Malang Regency had not played an active role in the development of local attractions. In Ngadas Village itself, the community already knew their identity as a tourism village. However, the involvement and participation of the community in the development process has not been optimal. The level of participation was measured using eight stages of Arnstein's participation, divided into four stages of participation; planning phase, implementation phase, phase of use and monitoring phase. The results indicate that the level of community participation in the traditional Ngadas tourism village is still the third of eight stages in Arnstein's participation. Characteristics of the third ladder, named informing are where the community is passively involved by only being informed about the activities and the plans to be carried out, which have been decided before. Opinions and ideas from the community are not being a consideration that can influence the decisions.